Improving a method for filtering images acquired from a space-based radar observation system based on the Kuan algorithm - Khudov, Hennadii; Makoveichuk, Oleksandr; Tokarev, Serhii; Andriushchenko, Artem; Pukhovyi, Oleksandr; Rohulia, Olexandr; Bilous, Oleh; Verovok, Mykola; Samoylenko, Valeriy; Khudov, Vladyslav (Eastern-European Journal of Enterprise Technologies, 2026)
The object of this study is the process of filtering images acquired from a space radar observation system. The task to filter images from a space radar observation system has been solved by applying the Kuan algorithm. The results reported here include the following: – the defined basic stages of the method for filtering images acquired from a space radar observation system based on the Kuan algorithm; – the performed experimental study on filtering images from a space radar observation system based on the Kuan algorithm. A method for filtering images from a space radar observation system based on the Kuan algorithm has been improved. Special features of the improved method, in contrast to those in established ones, are: – selection of a local filtering window; – calculation of local statistical characteristics; – calculation of variation coefficients; – calculation of the Kuan weight coefficient; – sequential filtering of image pixels using the “sliding” window method. A visual analysis of radar image filtering by an improved method based on the Kuan algorithm and known methods based on the Li algorithm and Frost algorithm were carried out. The use of the improved method when filtering an image acquired from a space radar surveillance system made it possible to increase the signal-to-noise ratio. That became possible due to the use of the Kuan algorithm. The choice of the Kuan algorithm has made it possible to achieve a 21% gain in the maximum signal-to-noise ratio in comparison with the known method (based on the Li algorithm). The scope of the improved method application includes filtering images from space radar surveillance systems. Conditions for practical implementation of the results are specialized software in software-hardware systems for processing radar images